A Systematic Review on Clinical Research and Approval Process - Nishabh, Kushwaha; N. Kshitija, Akarte (Asian Journal of Pharmaceutical Research and Development, 2023)
Drug discovery is a key step or process by which lead molecule is been optimized for further preclinical and clinical trial studies. Drug development process involves target identification, target validation, lead identification, and lead optimization. Once the lead molecule is optimized the HIT compound is been analyzed further in preclinical trial in animals and clinical trial in human subjects. The development of a new drug till marketing authorization should gone through several stages in order to make the drug safe, effective and should posses best quality to get approve for applicable regulatory requirements. The overall theme of our article is to review and state the process from drug discovery to approval for marketing of drug. The process from drug discovery till marketing authorization is time taking, complex and expensive so each target should be consider for development of new drug and new research tools must be used for any new drug development process. It takes around 10-15 years and US 1 billion for a new lead compound to make it as a medicine and to get marketing approval for general public use. On an average million lead molecules are been scrutinized to make a HIT compound, so that it can be use for further preclinical and clinical studies to make it available in market. This article provides a brief outline on stages from drug development to clinical research.